Human Capital Development Strategies In Micro, Small, And Medium Enterprises: A Qualitative Analysis Of Human Resource Management Practices - Herjanto, Taufan (STAI Denpasar Bali, 2023)
This qualitative study explores human capital development strategies in Micro, Small, and Medium Enterprises (MSMEs). The research aims to investigate HRM practices within MSMEs to identify effective strategies for human capital development. Employing a qualitative research model, semi-structured interviews and focus group discussions were conducted to gather data from a purposive sample of MSME owners and managers. Thematic analysis was utilized to analyze the data. The study revealed diverse approaches to human capital development, including training programs, mentorship, and performance evaluations. Moreover, it identified challenges such as resource constraints and skill mismatches. Overall, the findings contribute to understanding the nuanced dynamics of human resource management in MSMEs and provide insights for improving human capital development strategies in this sector.